A Study of Method Development, Validation, and Forced Degradation for Simultaneous Quantification of Paracetamol and Ibuprofen in Pharmaceutical Dosage Form by RP-HPLC Method - Jahan, Md. Sarowar (Anal Chem Insights, 2014)
A rapid and stability-indicating reversed phase high-performance liquid chromatography (RP-HPLC) method was developed for simultaneous quantification of paracetamol and ibuprofen in their combined dosage form especially to get some more advantages over other methods already developed for this combination. The method was validated according to United States Pharmacopeia (USP) guideline with respect to accuracy, precision, specificity, linearity, solution stability, robustness, sensitivity, and system suitability. Forced degradation study was validated according to International Conference on Harmonisation (ICH). For this, an isocratic condition of mobile phase comprising phosphate buffer (pH 6.8) and acetonitrile in a ratio of 65:35, v/v at a flow rate of 0.7 mL/minute over RP C18 (octadecylsilane (ODS), 150 × 4.6 mm, 5 μm, Phenomenex Inc.) column at ambient temperature was maintained. The method showed excellent linear response with correlation coefficient (R(2)) values of 0.999 and 1.0 for paracetamol and ibuprofen respectively, which were within the limit of correlation coefficient (R(2) > 0.995). The percent recoveries for two drugs were found within the acceptance limit of (97.0–103.0%). Intra-and inter-day precision studies of the new method were less than the maximum allowable limit percentage of relative standard deviation (%RSD) ≤ 2.0. Forced degradation of the drug product was carried out as per the ICH guidelines with a view to establishing the stability-indicating property of this method and providing useful information about the degradation pathways, degradation products, and how the quality of a drug substance and drug product changes with time under the influence of various stressing conditions. The degradation of ibuprofen was within the limit (5–20%, according to the guideline of ICH), while paracetamol showed <20% degradation in oxidation and basic condition.